PENGARUH PENGETAHUAN TENTANG LINGKUNGAN, SIKAP PADA LINGKUNGAN, DAN NORMA SUBJEKTIF TERHADAP NIAT PEMBELIAN GREEN PRODUCT - Adil, Afandie (Universitas Slamet Riyadi, 2015)
Purpose of this research to analyze the effect of knowledge about environment, attitude to the environment and subjective norms on purchase intention on green product. This study is a survey. The population is a consumer aged 17 years and over who know and understand about the green product in Surakarta. Sample of 100 people with convenience sampling data. Type data used quantitative and qualitative data. Source of data used primary data and secondary data. The technique of collecting data used questionnaires and literature. Data were analyzed used multiple linear regression. The results showed that the knowledge of the environment a significant effect on purchase intention green product. Attitude to the environment a significant effect on purchase intention green product. Subjective norms a significant effect on purchase intention green product. Attitude to the environment is the dominant variable effect on purchase intention green product. Keywords: knowledge about environment, attitude to the environment, subjective norms and purchase intention green product.